Intellectual property, trade and development - Gervais, Daniel J., 1963- (Oxford : Oxford University Press, 2014)
The author provides a comprehensive analysis of the latest economic, political and social research and advanced current thinking on the relationship between intellectual property and trade and development.
Previous edition: 2007.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 14, 2014).
Keywords: Agreement on Trade-Related Aspects of Intellectual Property Rights -- (1994 April 15); Intellectual property -- Economic aspects; Trade regulation -- Economic aspects; Law and economic development